Experimental and numerical studies on the effect of packed bed length on CO and NOx emissions in a plane-parallel porous combustor. (15th August 2019) - Shi, Junrui; Liu, Yongqi; Mao, Mingming; Lv, Jinsheng; Wang, Youtang; He, Fang
Abstract: Gas diffusion combustion in a plane-parallel packed bed filled with 2.5 mm alumina pellets is experimentally and numerically investigated. Special attention is focused on the influence of bed length ( h ) on the CO and NOx emissions for different excess air ratios ( α ) and gas mixture velocities ( u g, in ). It is found that h has significant influence on NOx emission when h  < 120 mm. NO emission decreases dramatically with h due to decrease in flame temperature in open space above the porous zone. However, the influence of h on NOx emission becomes less important when h  > 120 mm. Increase in h always leads to an linear increases in CO emission over the bed length range from 40 mm to 200 mm regardless of α and u g, in . For the lowest α (1.88), good performance regarding CO emission is observed, CO emission increases from 2 ppm to 49 ppm when h increases from 40 mm to 200 mm. Moreover, wide high temperature zone of the external combustor walls indicates that it is feasible to develop radiative burner based on diffusion filtration combustion. Highlights: Both experimental and numerical studies on diffusion filtration combustion. CO emission increases linearly with bed length ( h ) regardless of excess air ratio. NOx emission increases sharply with h when<120 mm. The Lowest NOx is obtained at the highest h of 200 mm. Flame temperature drops dramatically when<120 mm.